CHEMICAL AND SENSORY CHARACTERISTICS OF CARP MEAT (Osphronemus goramy) FROM DIFFERENT SIZES - Guswanda Putra; Bustari Hasan; Sumarto Sumarto (Berkala Perikanan Terubuk, 2019)
This research aims to evaluate and compare of proximate composition, amino acid and fatty acid of carp (Osphronemus goramy) from different sizes: small (400-500 gr), medium (600 – 800 g), and large (900-1100 g). 27 samples of carp were obtained from a cage in Gurami village, Kampar. The edible portion, processing waste, water holding capacity, sensory quality, proximate, amino acid and fatty acid were evaluated. The result showed that appearance, odor, edible portion, processing waste were not different between fish sizes. The highest taste and texture were found in large size carp (8.5 and 8.1), then followed by medium (8.3 and 7.9), and small (7.6 and 7.8), respectively. The highest water holding capacity was found in medium size carp (32.4%) then large (28.3%) and small (26.0%). The result of proximate analysis of the highest water and ash content were found in small size carp (75.55% and 1.05%), then followed by medium (74.20% and 0.90%) and large (7.69% and 0.88%). The protein content of large size carp (20.88%) was higher than medium (18.70%) and small (18.36%). The fat content of large size carp (2.70%) was higher than medium (2.40%) and small (2.29%). The highest amino acid was found in large size carp (69.25%) followed by medium (56.38%) and small (49.86%). The highest fatty acid was found in large size carp (99.55%) followed by small (97.63%) and medium (97.20%).